Analysis of Waiting List and Registration Cancellations for Hajj: (Case Study: Ministry of Religious Affairs in Padang City) - Husna, Nurul Lailatul Amini; Illahi, Ilham (Pascasarjana Universitas Pasundan, 2023)
The background of this research is the increasing number of people registering for Hajj every year so that in the implementation of restrictions on the departure of the Hajj quota in Indonesia which results in a long waiting period for Hajj in each region, especially in the city of Padang. The long waiting period for Hajj in Padang City has an impact on Prospective Hajj pilgrims which results in the cancellation of Hajj registration. This study aims to find out how the views of hajj organizers and prospective pilgrims at the Ministry of Religion of Padang City regarding the haj quota restrictions imposed by the government and to deal with public misunderstandings about these regulations. This study uses qualitative methods, where the research material is based on facts and data collection uses interview techniques. By conducting direct interviews with Hajj Organizers, the Ministry of Religion, Padang City. Based on the results of the research, with the perceptions of prospective pilgrims and hajj organizers of the Ministry of Religion of Padang City, the public, especially prospective pilgrims, can understand clearly and there are no more public misunderstandings about the haj quota restrictions. In addition, it is hoped that the haj organizers will be able to disseminate this information to prospective hajj pilgrims who are waiting for the pilgrimage to depart in Padang City so that all people get information regarding the determination of haj quotas evenly.